Sobre a pretensão à universalidade dos direitos humanos: paradoxos e exclusões - Caixeta, Davi Mendes (2018)
Human rights have been universally declared by important documents and international treaties, constitutionally guaranteed by several countries, in order to ensure the life, liberty, dignity of all people. Based on the human being, these rights were considered universal, inalienable, irrefutable. However, the political crises of the beginning of the twentieth century, such as world wars, nationalist conflicts, totalitarian governments, concentration camps, questioned the claim to the universality of human rights. Although they were affirmed as universal postulate for all mankind, many people and several social groups, like stateless persons and refugees, were totally deprived of fundamental guarantees, they were excluded from society. Thereupon, it is necessary to take a critical and sharp look at discourses involving the universality of these rights, to overcome a naive or idealized approach, and to consider how these rights were placed in a terrible paradox, revealing contradictions and exceptions. This research seeks to do a critical study about the claim to the universality of human rights, presenting and understanding the meaning of paradoxes and exclusions. The main question that inspires this work is: why are human rights, universally declared, denied on many occasions to many people and several social groups? The first approach discusses the paradoxes of universality contained in universal declarations, like the documents of 1789 and 1948. Another approach considers the problem of contradictions related to State, the sovereign, who declares and ensures rights, but also decides on cases of exception. This comment also highlights the situation of subjects who are excluded from society, and it analyzes paradoxes related to citizenship. The category of stateless persons emerges, they are rejected by society, excluded by State, deprived of all rights. Thereby, there is an intension to contribute to the dialogue on human rights, considering, mainly, people who are being excluded every day